Analisis Sentimen dalam Memprediksi Hasil Pemilu Presiden dan Wakil Presiden : Systematic Literature Review - Oktaviami Manullang; Cahyo Prianto (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2023)
In this research, an analysis of public sentiment towards the presidential and vice presidential candidates will be carried out through the Twitter social network. Sentiment analysis has become an interesting topic in predicting the results of this election, therefore the writing in this paper summarizes the use of sentiment analysis in the presidential election from 2014 to 2019. Looking at the public's response to presidential and vice presidential candidates on social media, especially Twitter, there is responding positively and negatively. The purpose of this journal is to compare methods for predicting public response to elections, and to conduct a systematic review of the literature to identify, review, and synthesize research related to the use of sentiment analysis in predicting the results of the Presidential and Vice-Presidential elections.